2013
DOI: 10.1142/s0218810413500275
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Uncemented Trapezio-Metacarpal Cups: A Finite Element Study

Abstract: Trapezium components from two uncemented total joint replacements were compared in a three-dimensional finite element model. A 100 N axial and angular load was applied in a normal and an osteoporotic bone model. The axial deformation and maximum periprosthetic stress are greater for the Elektra than the Motec CMC cup. The Motec CMC design is less sensitive to changing bone quality. The Elektra cup transmits more stress to the cortical bone rim in all load conditions, but under angular loading the proportionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Finite element analysis has shown that conical cups with a center of rotation at the bone surface deliver less stress to the cortical bone rim during angular loading of 30° compared with conical cups with a center of rotation that is above the bone surface [30]. The extrinsic center of rotation was probably the main cause of early failures with the Motec (Swemac AB, Linköbing, Sweden) cup design [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Finite element analysis has shown that conical cups with a center of rotation at the bone surface deliver less stress to the cortical bone rim during angular loading of 30° compared with conical cups with a center of rotation that is above the bone surface [30]. The extrinsic center of rotation was probably the main cause of early failures with the Motec (Swemac AB, Linköbing, Sweden) cup design [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Design and poor primary press fit fixation leading to lack of osteointegration has been proposed as a reason for early cup loosening (Hansen and Snerum, 2008;Hansen et al, 2011;Thorkildsen et al, 2013), whereas late loosening may be caused by a local reaction to metal particles (Fabi et al, 2012;Milosev et al, 2006;Willert et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the main reason for revision was loosening of the trapezium cup, which accounts for up to 76% of revisions (Hansen and Snerum, 2008; Hernandez-Cortes et al, 2012; Klahn et al, 2012). Design and poor primary press fit fixation leading to lack of osteointegration has been proposed as a reason for early cup loosening (Hansen and Snerum, 2008; Hansen et al, 2011; Thorkildsen et al, 2013), whereas late loosening may be caused by a local reaction to metal particles (Fabi et al, 2012; Milosev et al, 2006; Willert et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques used for the evaluation of large joint implants have been adapted to TMC joint implants. One method is finite element analysis, which is a computer-based simulation of load transfer from implants to the adjacent bone (Thorkildsen et al., 2013). Radiostereometric analysis is another method; it allows precise in vivo assessment of implant fixation.…”
Section: Total Joint Arthroplastymentioning
confidence: 99%
“…In this way implant designs with a high risk of later aseptic loosening and need for revision can be detected within 2 years after operation rather than having to wait longer (Ryd et al., 1995). These techniques have helped understand the reasons for failure in some implant designs and taught us that trapezium components with a collar and a high centre of rotation, such as the Motec implant (Swemac AB, Linköbing, Sweden), carry an increased risk of failure (Thillemann et al., 2016; Thorkildsen et al., 2013). At present the implants with the best results are all collarless designs with a low centre of rotation in the cup.…”
Section: Total Joint Arthroplastymentioning
confidence: 99%